Comparison of Village Cooperative (KUD) and Village-Owned Enterprises (BUM Desa) in Indonesia - Miftakhul Choiri (Bulletin of Islamic Economics, 2022)
This paper aims to seek the difference between Village Unit Cooperatives (KUD) and Village Owned Enterprises (BUM Desa). This paper also seeks to observe the impact of the establishment of BUM Desa on KUD and the possibility of synergy between the two institutions. In this study, the methodology used is normative legal research with a comparative approach. This research shows that both institutions have the same goal, namely to enhance the village community’s quality of life. Even so, BUM Desa has a wider scope of business than KUD. In addition, this study also shows the possibility of synergies between the two business entities. Empirical studies are very open and needed to strengthen the synergy idea between the two business entities. The originality of this paper is because it examines the legal and socio-economic aspects of KUD and BUM Desa.